2000
DOI: 10.1007/bf03168337
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound grayscale image compression with JPEG and wavelet techniques

Abstract: The purpose of the study was to evaluate the effects of Iossy compression on grayscale ultrasound images to determine how much compression can be applied while still maintaining images that are acceptable for diagnostic purposes. The study considered how the acquisition technique (video frame-grabber versus directly acquired in digital forro) influences how much compression can be applied. For directly acquired digital images, the study considered how text (that is burned into the image) affects the compressib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…We compared several sets of filters and finally retained the 10/6 filter pair described in [12, p. 127]. The corresponding symmetric components in (1) are (2) (3)…”
Section: Choice Of the Wavelet Filtersmentioning
confidence: 99%
“…We compared several sets of filters and finally retained the 10/6 filter pair described in [12, p. 127]. The corresponding symmetric components in (1) are (2) (3)…”
Section: Choice Of the Wavelet Filtersmentioning
confidence: 99%
“…Compression of medical images is vital in achieving a low bit rate in the representation of radiology images in order to reduce the data volume, without loss in diagnostic information [12,13]. Persons et al discussed diagnostic accuracy and reported that reconstructed medical images with a compression ratio of 9:1 do not result in visual degradation [14]. Li et al investigated the effect of JPEG and wavelet compression algorithm on medical images and concluded that compression ratio up to 10:1 is acceptable [15].…”
Section: Introductionmentioning
confidence: 99%
“…In a very recent follow-up study on the compression of ultrasound images, Persons et al [10] compared JPEG-and SPIHT-compressed ultrasound images at low compression rates and concluded that for both, JPEG and SPIHT produced diagnostically acceptable images at a 10 : 1 compression ratio. However, at compression rates above 12 : 1, the SPIHT approach developed artifacts, such as lack of low-contrast detail, which impacted the diagnostic acceptability.…”
mentioning
confidence: 99%